Análise e síntese geométrica de antenas duplo-refletoras para cobertura omnidirecional - Silva, Lucas Ribeiro Gomes da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work presents algorithms for the synthesis of classic reflectors and modeled reflectors for antennas of two reflectors with omnidirectional coverage, based on the principles of geometric optics( GO - Geometrical Optics). The analyzed configurations are: ADE (Axis-Displaced Elipse) and ADC (Axis-Displaced Cassegrain)). In addition to the geometric synthesis algorithm soft reflectors, an electromagnetic analysis of these antennas and a coaxial horn operating in the TEM modeis performed (Transverse Electromagnetic Modes), taking into account that the reflector surfaces are perfect electrical conductors (PEC -perfect electric conductor), from radiation diagrams and reflection coefficient graphs using a moment method algorithm (MoM -Methodo f Moments). The analysis of radiation diagrams and return loss graphs takes into account the change in control parameters: 1, 2 and 3. In this way, the interference of these parameters in the antenna efficiency is demonstrated, and with this an optimum point is studied between the directivity of the antennas and the levels of secondary lobes, in order to improve the efficiency of the se antennas, in terms of directivity and azimuth direction of interest.

Este trabalho apresenta algoritimos de síntese de refletores clássicos e de refletores modelados para antenas de dois refletores com cobertura omnidirecional, tomando como base os princípios da óptica geométrica (GO – Geometrical Optics). As configurações analisadas são: ADE(Axis-Displaced Elipse) e ADC (Axis-Displaced Cassegrain)). Além dos algoritmos de síntese geométrica dos refletores, é feita a análise eletromagnética dessas antenas e de uma corneta coaxial operando no modo TEM (Transverse Electromagnetic Modes), levando em conta que as superfícies dos refletores são condutores elétricos perfeitos (PEC -perfectelectricconductor), a partir de diagramas de radiação e gráficos de coeficiente de reflexão por meio de um algoritmo de método dos momentos (MoM -Method of Moments). As análises dos diagramas de radiação e dos gráficos de perda de retorno levam em conta a alteração de parâmetros de controle: 1, 2 e 3. Dessa forma, é demonstrada a interferência desses parâmetros na eficiência das antenas, e com isso é estudado um ponto ótimo entre a diretividade das antenas e os níveis de lóbulos secundários, a fim de melhorar a eficiência dessas antenas, em termos de diretividade e direção azimutal de interesse.
Analysis and geometric synthesis of dual-reflective antennas for omnidirectional coverage
Keywords: Antenas (Eletrônica); Óptica geométrica; Telecomunicações